(untitled) (Quinto Sol, 2013)
The objective of this paper is to analyze the particular characteristics and conditions of an economic model, which with some variations, was maintained in the North Patagonian region from the late colonial period until the military campaigns of 1879, which subdued and destroyed the indigenous world. This permanence was the product of a continuous readjustment of border relations within the framework of the dominant order, which involved numerous indigenous groups on both sides of the Andes mountain range with different Spanish-Creole segments.